2020
DOI: 10.4155/fmc-2020-0194
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel Quinic Acid Derivatives: In Vitro Cytotoxicity and Anticancer Effect on Glioblastoma

Abstract: Aim: Quinic acid (QA) is a cyclic polyol exhibiting anticancer properties on several cancers. However, potential role of QA-derivatives against glioblastoma is not well established. Methodology & results: Sixteen novel QA-derivatives and QA-16 encapsulated poly (lactic-co-glycolic acid) nanoparticles (QA-16-NPs) were screened for their anti-glioblastoma effect using standard cell and molecular biology methods. Presence of a tertiary hydroxy and silylether groups in the lead compound were identified for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“… 120 Moreover, Murugesan et al observed the cytotoxic impact of quinic acid derivatives on human glioblastoma cell lines SNB19 and LN229. 121 Consequently, the list of bioactive metabolites detected in the CIR extract ( Table 1 ) aligns with the observed antiproliferative potential of the CIR extract against various types of cancer cells.…”
Section: Resultssupporting
confidence: 57%
“… 120 Moreover, Murugesan et al observed the cytotoxic impact of quinic acid derivatives on human glioblastoma cell lines SNB19 and LN229. 121 Consequently, the list of bioactive metabolites detected in the CIR extract ( Table 1 ) aligns with the observed antiproliferative potential of the CIR extract against various types of cancer cells.…”
Section: Resultssupporting
confidence: 57%
“…Numerous flavonoids, terpenoids and polyphenols, are known to inhibit carcinogenesis and tumorigenesis in vivo and in vitro. Among the identified compounds 2(5H)-Furanone (86)(87)(88)(89) along with phytol (90,91) and QA (92,93) are used in the treatment of several types of cancer. Since it is the predominant component identified by GC-MS, it could be the predominant anticancer and anti-inflammatory component of the extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Murugesan et al proposed quinic acid derivatives as potential inhibitors of GBM cells. 98 A total of 16 quinic acid derivatives were synthesized and evaluated in LN229 and SNB19 cell lines, where 160 showed promising anti-proliferative activity, with IC 50 = 10.66 and 28.22 μM, respectively. Furthermore, 160 was formulated into nanoparticles, which showed a similar effect as 160 alone, and biological studies confirmed that 160 induces apoptosis through the ROS-mediated pathway and caspase 3/7 ( Figure 41 A).…”
Section: Recent Medicinal Chemistry Campaignsmentioning
confidence: 99%
“…Murugesan et al proposed quinic acid derivatives as potential inhibitors of GBM cells . A total of 16 quinic acid derivatives were synthesized and evaluated in LN229 and SNB19 cell lines, where 160 showed promising anti-proliferative activity, with IC 50 = 10.66 and 28.22 μM, respectively.…”
Section: Recent Medicinal Chemistry Campaignsmentioning
confidence: 99%
See 1 more Smart Citation